Spatial distribution and statistical properties of small-scale convective vortex-like motions in a quiet-Sun region - Vargas Domínguez, S. (2011)
High-resolution observations of a quiet-Sun internetwork region taken with the Solar 1-m Swedish Telescope in La Palma are analysed. We determine the location of small-scale vortex motions in the solar photospheric region by computing the horizontal proper motions of small-scale structures on time-series of images. These plasma convectively driven swirl motions are associated to (1) downdrafts (that have been commonly explained as corresponding to sites where the plasma is cooled down and hence returned to the interior below the visible photospheric level) and (2) horizontal velocity vectors converging on a central point. The sink cores are proved to be the final destination of passive floats tracing plasma flows towards the centre of each vortex. We establish the occurrence of these events to be 1.4 × 10-3 and 1.6 × 10-3 vortices Mm-2 min-1, respectively, for the two time-series analysed here.